Tradisi Panjang Mulud pada Perayaan Maulid Nabi Muhammad SAW - Izar Mutaqin; Abdul Aziz; Elan Herlangga; Ahmad Maftuh Sujana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Panjang Mulud tradition is one form of local wisdom that has developed in society as part of the celebration of the birth of Prophet Muhammad (Maulid Nabi Muhammad SAW). This study aims to describe the meaning, symbolism, and the cultural and religious values embedded in the tradition. Using a descriptive qualitative approach, data were collected through observation, interviews, and literature studies on the implementation of Panjang Mulud in various regions, particularly in Java. The results show that Panjang Mulud is not merely a ceremonial celebration, but also a form of reverence for the Prophet Muhammad and a manifestation of social solidarity and the preservation of local culture. This tradition is rich in spiritual, social, and educational values that help strengthen the religious and cultural identity of the community. Therefore, Panjang Mulud is an important part of cultural heritage that deserves to be preserved amid the currents of modernization and globalization.